Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P. (Journal of Materials Chemistry C, 2016)
Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1,3,6,8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1,3,6,8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA) and a phenothiazine substituent (PY-PH) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance. PY-CA exhibited the maximum brightness at around 2500 cd m(-2) and the power efficiency of 1.5 lm W-1 while that of PY-PH exhibited 2116 cd m(-2) and 0.45 lm W-1 respectively.

New pyrene cored small organic molecule with a flexible alkyl spacer: a potential solution processable blue emitter with bright photoluminescence - Valsange, Nitin G.; Wong, F. L.; Shinde, Durgaprasad; Lee, C. S.; Roy, V. A. L.; Manzhos, Sergei; Feron, K.; Chang, Samuel; Katoh, Ryuzi; Sonar, Prashant; Wadgaonkar, Prakash P. (New Journal of Chemistry, 2017)
A new pyrene cored small organic molecule viz. 1,3,6,8-tetrakis(4-((5-(9H-carbazol-9-yl) pentyl)oxy) phenyl)pyrene (PY-II) was designed and synthesized. The carbazole moiety with an alkyl spacer was introduced at 1, 3, 6 and 8 positions of the pyrene core to improve the charge transport properties and solution processability. PY-II exhibited excellent solubility in common organic solvents and high thermal stability up to 345 degrees C. The photoluminescence quantum yield (PLQY) of PY-II in solution was found to be 0.9 with bright blue emission near 450 nm which is just appropriate for the human eye. The solution processed non-doped OLED device fabricated using PY-II as an emissive layer afforded a pure blue emission with CIE coordinates of 0.16 and 0.16, a power efficiency of 0.17 lm W-1, a maximum current efficiency of 0.41 cd A(-1) and a maximum brightness of 202 cd m(-2).